Penerapan Sistem Manajemen Mutu Elektronik (E-Smm) dalam Menjamin Kepatuhan Cdob pada Pedagang Besar Farmasi (Pbf) - Herman Widjaja; Putriana Aulia; Hutri Kiasatina; Lupita Mardia; Jingga Stacia Febiola; Syifa Elsyadai; Siti Nadya; Amanda Sulistiawaty (Institut Nalanda, 2026)
The implementation of the Electronic Quality Management System (e-SMM) in Pharmaceutical Wholesalers (PBF) has emerged as a strategic approach to improving quality assurance and ensuring compliance with Good Distribution Practice (CDOB) regulations in pharmaceutical distribution. This study aims to analyze the contributions, benefits, and challenges associated with the implementation of e-SMM in PBF through a literature review using a qualitative descriptive approach. The findings reveal that e-SMM significantly improves operational efficiency by digitalizing quality management documents, reducing manual administrative tasks, and facilitating faster access to information. The system also enhances data integrity and traceability through electronic audit trails, enabling accurate monitoring of document revisions and user activities. In addition, automated reminder features support timely calibration of equipment, personnel training, and scheduled quality activities, while integration with warehouse temperature monitoring systems helps maintain product stability and storage compliance. Despite these advantages, the implementation of e-SMM faces several challenges, including substantial initial investment in information technology infrastructure, software validation, cybersecurity measures, and employee training. Organizational readiness and resistance to transitioning from conventional paper-based systems to digital workflows also remain significant barriers. Overall, e-SMM plays a crucial role in strengthening transparent, efficient, and reliable pharmaceutical quality management systems while supporting sustainable regulatory compliance and continuous quality improvement.